A systematic review of the urban green spaces for the city sustainability and attractiveness: a case study of jaffna city in northern province of sri lanka - Mathivathany, V. (University of Jaffna, 2016)
Development should be based on a balanced and harmonious relationship between social needs, economic activities and the environmental services to achieve sustainability of a city. Accordingly, aspects such as the “amount of urban green spaces per inhabitant, “public parks,” are considered to be of significant strategic importance and it making a city livable, pleasant, and attractive for citizens. This too gives a salutary effect on the growth of the City. Urban green parks serve as places of identity, memory, and belonging, enrich human life with meaning and emotions which is a key component of sustainability. Urban parks play a strategic meaning for the quality of life of our increasingly urbanized society. Jaffna city is a fast growing centre in north part of the country. But attention to the natural components and the green spaces of the urban structure is still poor. Therefore this paper aims to study the importance of urban parks for the sustainability of the city. Both secondary and primary data have been gathered. Primary data have been collected through a survey conducted among visitors of the parks. Questionnaires have been distributed in different hours of the day. Basic descriptive statistics and Multi criteria analysis have been applied in spatially. As a result, the majority (almost 78%) of the respondents indicated dissatisfaction with the services and amount of urban green currently present in the Jaffna. Valuation of these green spaces of urban areas should be integrated into project assessments' procedure and be properly accounted for in policy decisions and urban planning strategies. This study helps to City planners, urban designers and decision makers.
Keywords: Sustainability; City livable; urbanized society; urban planning; Green spaces